Direct observation of monoclinic ferroelectric phase and domain switching process in (K0.25Na0.75)NbO3 single crystals. Issue 14 (14th April 2015) - Deng, Hao; Zhang, Haiwu; Zhao, Xiangyong; Chen, Chao; Wang, Xi'an; Li, Xiaobing; Lin, Di; Ren, Bo; Jiao, Jie; Luo, Haosu
<x xml:space="preserve">Abstract</x> The domain-switching process of monoclinic K0.25Na0.75NbO3 single crystals were studied by in situ polarized light microscopy and X-ray diffraction.